(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Agriculture is on the cusp of a revolution, driven by the Internet of Things (IoT), which promises to usher in an era of intelligent farming for sustainable and efficient food production. This paper explores the integration of IoT-driven technologies in agriculture and assesses their potential to enhance productivity, sustainability, and resource efficiency. We review the range of IoT technologies currently employed, including advanced sensors, autonomous vehicles, drones, and data analytics platforms, and discuss how they contribute to precision agriculture practices. By analyzing case studies and current research, the paper highlights the improvements in water and energy use efficiency, reduced reliance on chemical inputs, and increased yield outcomes. Moreover, we examine the challenges faced in adopting such technologies, encompassing economic, technical, and social barriers, and environmental concerns. The paper also delves into future trends, such as the convergence of IoT with artificial intelligence, blockchain, and other cutting-edge technologies, and their anticipated impact on the agricultural sector. Finally, we discuss policy implications and offer recommendations for stakeholders to facilitate the transition towards an IoT-enabled sustainable future for agriculture. The findings indicate that while significant challenges remain, the intelligent application of IoT technologies in farming holds great promise for meeting the increasing global food demands without compromising the health of our planet.